Expression profile of CYP402C1 and its role in resistance to imidacloprid in the whitefly, Bemisia tabaci. (13th June 2022) - Guo, Lei; Zhang, Zhuang; Xu, Wei; Ma, Jiangya; Liang, Ni; Li, Changyou; Chu, Dong
Abstract: Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) is a cosmopolitan insect pest causing serious damage to crop production. Cytochromes P450 (CYPs) of B. tabaci are widely known to be involved in the metabolic resistance to a variety of insecticides, continuously increasing the difficulty in controlling this pest. In this study, four P450 genes ( CYP6CM1, CYP6CX1, CYP6CX3, and CYP402C1 ) in B. tabaci exhibited correlations with the resistance to imidacloprid. We have focused on trying to understand the function and metabolism capacity of CYP402C1 . The expression profiles of CYP402C1 were examined by reverse transcription quantitative real‐time PCR and fluorescence in situ hybridizations. Its role in resistance to imidacloprid was investigated by RNA interference, transgenic Drosophila melanogaster, and heterologous expression. The results showed that CYP402C1 was highly expressed in the active feeding stages of B. tabaci, such as nymphs and female adults. CYP402C1 was mainly expressed in midguts of nymphs and adults, especially in the filter chamber. Knockdown of CYP402C1 significantly decreased the resistance of B. tabaci to imidacloprid by 3.96‐fold (50% lethal concentration: 186.46 versus 47.08 mg/L). Overexpression of CYP402C1 in a transgenic D. melanogaster line (Gal4 > UAS‐ CYP402C1 ) significantly increased the resistance to imidacloprid from 12.68‐ to 14.92‐fold (129.01 and 151.80 mg/L versus 1925.14 mg/L). The heterologous expression of CYP402C1 showed a metabolism ability of imidacloprid (imidacloprid decreased by 12.51% within 2 h). This study provides new insights for CYP402C1 function in B. tabaci and will help develop new strategies in B. tabaci control and its insecticide resistance. Graphical Abstract: CYP402C1 was mainly distributed in the midguts of the nymphs and adults of Bemisia tabaci, especially in the filter chamber. Knockdown of CYP402C1 in the resistance population significantly decreased the resistance of B. tabaci to imidacloprid. Overexpression of CYP402C1 in a transgenic Drosophila melanogaster line significantly increased the resistance to imidacloprid.